The missing link: How university managers mediate the impact of a performance-based research funding system. Issue 1 (11th December 2018) - Krog Lind, Jonas
Abstract: The impact of Performance-based Research Funding System (PRFS) has received increasing attention in recent years. However, the literature has focused on individual-level or country-level effects, mostly ignoring the 'missing link' between PRFSs and their effects: university managers. Drawing upon the sociology of numbers and theories of organizational translation, this article uses the concepts of actionability and legitimacy to analyse how and why managers at two Danish universities undertook local translations of a new Bibliometric Research Indicator (BRI). While scholars have emphasized how research evaluation systems can be either strong or weak by design, this study demonstrates how local managers to some extent make national systems strong or weak. The study also finds though that managers' translations are conditioned by a range of background factors. These factors are identified as financial incentives, problem definitions, indicator competition, and identity and culture .